Problematika pembelajaran bahasa Arab: studi kasus pada siswa Sanggar Bimbingan Permai Penang Malaysia - Setianingsih, Rofiqoh; Robbani, A. Syahid (Diglosia: Jurnal Kajian Bahasa, Sastra, dan Pengajarannya, 2024)
Sanggar Bimbingan Permai Penang Malaysia is a nonformal institution that teaches Arabic to their students who are the children of Indonesian migrants. Same with other educational institutions, Arabic learning at Sanggar Bimbingan is not free from various problems. Therefore, this research aims to examine both linguistic and nonlinguistic issues in the teaching of Arabic at Sanggar Bimbingan Permai Penang, Malaysia. This research is a case study with a qualitative approach. The research respondents include the principal, teachers, students in grades III, V, and VI, and parents of students. Data was collected through participant observation and interviews. Observations were conducted for 28 days by directly teaching 24 students in three classes, with Arabic classes held three times a week. Interviews were conducted with one principal, three teachers, and two students. Data was analyzed using the Miles & Huberman technique, which involves data collection, reduction, presentation, and conclusion drawing. The research found linguistic problems including the complexity of Arabic grammar, the vastness of vocabulary, and differences between Arabic and the students’ native languages. Non-linguistic challenges encompass student motivation, environmental support, availability of study time, teaching quality, and inadequate facilities and infrastructure.